2005
DOI: 10.1590/s1135-57272005000600002
|View full text |Cite
|
Sign up to set email alerts
|

¿Es el plomo empleado en deportes (caza, tiro y pesca deportiva) un problema de salud pública infravalorado?

Abstract: INTRODUCCIÓNEl plomo (Pb) es el metal pesado que históricamente más problemas sanitarios y de contaminación ha causado en el mundo [1][2][3][4] . A pesar de las muchas medidas adoptadas en contra de su utilización en las últimas dos o tres décadas 1,2,[4][5][6] , su pertinaz presencia en el aire, suelo, agua y alimentos sigue considerándose todavía un factor de riesgo de primera magnitud, en especial para niños 1,3,5 y para algunos animales silvestres 4,6,7 . No en vano, hasta principios del siglo XX fue, tras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 81 publications
(128 reference statements)
3
5
0
1
Order By: Relevance
“…In turn, our consumption estimation was in concordance with Guitart and Thomas (2005) and Lazarus et al (2008), who highlighted that big game meat is most consumed by hunters and their families.…”
Section: Consumption Of Red Deer and Wild Boar Meatssupporting
confidence: 85%
See 2 more Smart Citations
“…In turn, our consumption estimation was in concordance with Guitart and Thomas (2005) and Lazarus et al (2008), who highlighted that big game meat is most consumed by hunters and their families.…”
Section: Consumption Of Red Deer and Wild Boar Meatssupporting
confidence: 85%
“…This fact was also indicated in other studies (Guitart and Thomas 2005;Lazarus et al 2008). Lazarus et al (2008) suggested that the specific group, hunters and their families, presents a greater intake of toxic metal species than the general population.…”
Section: Risk Assessmentsupporting
confidence: 71%
See 1 more Smart Citation
“…In Spain, where it is estimated that hunting and shooting are responsible for the dispersion in nature of about 6000 tonnes of Pb per year [172,173], there are over 770 shooting ranges [10,174]. According to a local hunting foundation [175], hunting is practiced by 1.6% of the population of the Basque Country (northern Spain).…”
Section: Effectiveness Of Agro-industrial Wastes As Amendments For Thmentioning
confidence: 99%
“…En los últimos años, se han adoptado medidas contra el uso del Pb; sin embargo, su persistencia en el aire, suelo, agua y alimentos, sigue considerándose un factor de riesgo, en especial para los niños (Needleman, 2004). En el suelo se encuentra principalmente en forma de Pb 2+ , el cual forma compuestos insolubles tales como: Pb (OH) 2 , PbCO 3 , PbS, PbSO 4 (Guitart y Vernon, 2005). Ambientes contaminados con Pb crean un ambiente desfavorable para el crecimiento y sobrevivencia de comunidades de microorganismos, debido a que este metal causa daño en el ADN genómico, en lípidos y proteínas, y además reemplaza iones metales esenciales como Zn, Ca y Fe presentes en las proteínas.…”
Section: Introductionunclassified